Pemberdayaan Masyarakat Melalui Penerapan Teknologi Tepat Guna dalam Pengelolaan Sampah Berbasis Ekonomi Hijau di KSM Sido Resik, Imogiri, D.I.Yogyakarta, Indonesia - Warisaura, Angge Dhevi; Sukmawati, Paramita Dwi; Bikorin, Bikorin (Jurnal Hilirisasi IPTEKS, 2025)
Padukuhan Dukuh, located in Imogiri Subdistrict, Bantul Regency, Indonesia, is experiencing critical waste management challenges, particularly after the permanent closure of the Piyungan Regional Final Disposal Site on May 1, 2024. Bantul generated approximately 434.05 tons of waste per day in 2024, yet only around 13% was managed by the provincial government. In response, Imogiri Village initiated decentralized, community-based waste management, including the establishment of KSM Sido Resik in Padukuhan Dukuh. However, limited technological capacity and weak managerial practices have constrained the quality and quantity of organic and inorganic waste processing. This study aims to strengthen community-based waste management through the adoption of appropriate technology and capacity-building interventions. A participatory, community-based approach was implemented over six months, consisting of socialization, hands-on training, technology installation (organic waste chopper and plastic shredder), and continuous mentoring. Evaluation was conducted using pre–posttests, production monitoring, and structured interviews. Results show that composting duration decreased from ±60 days to approximately 30 days, with production capacity increasing from 10 kg to 35 kg per two-month cycle. Plastic waste value increased from IDR 1,500/kg to IDR 5,500/kg after shredding. Community income rose from IDR 500,000/month to over IDR 1,500,000–2,000,000/month. Skill assessments indicate up to a 80% improvement in technical and managerial competencies. The findings demonstrate that integrating appropriate technology with community-driven management effectively enhances waste valorization, supports circular economy practices, and strengthens local socio-economic and environmental resilience.